Defecatory urge increases cognitive control and intertemporal patience in healthy volunteers. Issue 7 (16th April 2019) - Zhao, Dongxing; Corsetti, Maura; Moeini‐Jazani, Mehrad; Weltens, Nathalie; Tuk, Mirjam; Jan, Tack; Warlop, Luk; Van Oudenhove, Lukas
Abstract: Background: Past research has demonstrated that moderate urge to urinate improves inhibitory control, specifically among participants with higher behavioral inhibition sensitivity (BIS). The effect was absent when the urge exceeded intolerable level. The present research examines whether rectal distension‐induced urge to defecate has similar effects. Methods: The moderate and high defecatory urge were induced by rectal distension in healthy volunteers (n = 35), while they completed Stroop task and monetary delay discounting task. The difference of average reaction time between incongruent and congruent trials in the Stroop task (Stroop interference) and the preference for larger‐later rewards in the delay discounting task were the primary outcomes. Key Results: Participants with high BIS (n = 17) showed greater ability to inhibit their automatic response tendencies, as indexed by their Stroop interference, under moderate urge relative to no urge (128 ± 41 ms vs 202 ± 37 ms, t 64  = 2.07; P  = 0.021, Cohen's d : 0.44), but not relative to high urge (154 ± 45 ms, t 64  = 1.20; P  = 0.12, Cohen's d : 0.30). High BIS participants also showed a higher preference for larger‐later reward in the delay discounting task under high (odds ratio = 1.51 [1.02‐2.25], P  = 0.039) relative to no urge, but not relative to moderate urge (odds ratio = 1.02 [0.73‐1.42], P  = 0.91). In contrast, rectal distension did not influence performance on either of the tasks in participants with low BIS (n = 18). Conclusions and inference: These findings may be interpreted as a "spill‐over" effect of inhibition of the urge to defecate to volitional cognitive control among healthy participants with high BIS. Abstract : Defecatory urge improves inhibitory control in healthy volunteers. Inhibition of the urge to defecate facilitated cognitive control under moderate urge, and increased preference for larger‐later rewards in the delay discounting task under high urge, among healthy humans with high behavioral inhibition sensitivity (BIS), but not among those with low BIS. These results demonstrate that mechanical signals originating in the rectum that require inhibition can improve inhibitory control in other domains, and contribute to studies on cognitive function in functional GI disorders.